PERAN LSM PATTIRO SEMARANG MENDORONG DINAS PENDIDIKAN KOTA SEMARANG UNTUK MEWUJUDKAN KETERBUKAAN INFORMASI PUBLIK - Sandy Jolosangoro; Yuwanto .; Nunik Retno H (Journal of Politic and Government Studies, 2014)
Public information disclosure is one of the spirits of good governance. To embodypublic information disclosure required a balanced engagement betweengovernment and civil society. The involvement of civil society becomes animportant element, because it may contribute to assist and oversees theimplementation of public information disclosure.Dinas Pendidikan Kota Semarang is the agency that has fairly complexinstitutional structure. Information technology to support the provision of publicinformation services owned by the Dinas Pendidikan Kota Semarang quiteadvanced compared to other agencies. But it is ironically the strengtheningimplementation of public information disclosure in its environment less than themaximum.To support Dinas Pendidikan Kota Semarang embodies public informationdisclosure, requires the involvement of civil society elements. The involvement ofcivil society becomes an important element, because it may contribute to assistand oversees the implementation of public disclosure in Dinas Pendidikan KotaSemarang. NGO Pattiro Semarang to be partner of the government to implementand simultaneously escorting public information disclosure. In addition NGOvisions also aims to promote the establishment of good governance, one of whichis public information disclosure.This research uses descriptive qualitative research method. The data collectiontechnique uses documentation studies and interviews to Semarang Pattiro activistsas key informants, as well as PPID Dinas Pendidikan Kota Semarang assupporting informant.The results of the study suggested that the role of Pattiro Semarang is realizedthrough SIAP II program and strengthening public information disclosurecooperates with USAID and GIZ. After the program, the implementation forms ofpublic information disclosure have some progress such as the PPID, SOPformation of public information services, public information categorization, anddevelopment of a public information service system. In carrying out its role,Pattiro Semarang has supporting factors. They are the experience awakened a longcollaboration with Dinas Pendidikan, Pattiro Semarang relationship intelligence toother NGOs, and good image as an independent NGO in the eyes of thegovernment. While the major obstacles were the lack of public awareness of theright to obtain public information and the minimum commitment budget of DinasPendidikan to strengthen public information disclosure.2Keywords: Public information disclosure, NGO, Pattiro Semarang, DinasPendidikan